Information in prices about future earnings - Kothari, S.P; Sloan, Richard G (Journal of Accounting and Economics, 1992)
Stock return over a period reflects the market's revision in expectation of future earnings. Accounting earnings over the same period, however, have limited ability to reflect such revised expectations. Therefore, returns anticipate earnings changes and the earnings response coefficient from a regression of returns on contemporaneous earnings changes is biased toward zero. We reduce this bias by including leading-period returns in price-earnings regressions. The resulting estimated earnings response coefficient magnitudes suggest that the capital market, on average, views earnings changes to be largely permanent. This is consistent with the random walk time series property of annual earnings.